Balancing Profit and Transparency: How CSR, Green Innovation, and Board Diversity Drive Carbon Disclosure in Indonesia - Haryanto, Hery; Suprapto, Yandi; Santi, Santi (Universitas Muhammadiyah Yogyakarta, 2025)
Research aims: This study explores how Corporate Social Responsibility (CSR), Green Innovation, and Board Gender Diversity influence Carbon Emission Disclosure (CED), with Return on Assets (ROA) as a moderating variable, specifically among Indonesian manufacturing companies.Purpose: This study aims to examine how sustainability practices and board inclusivity contribute to the transparency of carbon emission disclosures and to investigate whether corporate profitability enhances the commitment to environmental reporting among manufacturing firms in Indonesia.Methodology: With a quantitative approach on manufacturing firms listed on the IDX (2019–2023). Data is collected through purposive sampling from annual reports and sustainability reports. Research findings: CSR and gender diversity on corporate boards positively affect carbon emission disclosure, whereas ROA and green innovation exhibit varying effects. Although strong financial performance may reduce transparency in disclosure, the outcomes align with stakeholder theory and legitimacy theory perspectives.Originality/Theoretical contribution: This study introduces ROA as a moderating variable, which is rarely used in carbon disclosure studies, particularly in Indonesia. It demonstrates how financial performance affects transparency. This paper addresses a research gap by comparing Indonesia's wegapclosure procedures with international advanced practices and the relevant practices in external business initiatives to foster sustainability.